The Role of Genistein in Mammalian Reproduction - Gabriella Guelfi; Rolando Pasquariello; Polina Anipchenko; Camilla Capaccia; Georgia Pennarossa; Tiziana A. L. Brevini; Fulvio Gandolfi; Massimo Zerani; Margherita Maranesi (Molecules, 2023)
Genistein is a natural compound belonging to flavonoids, having antioxidant, anti-inflammatory, and anti-neoplastic properties. Genistein is considered a phytoestrogen. As such, genistein can bind estrogen receptors (ERα and ERβ), although with a lower affinity than that of estradiol. Despite considerable work, the effects of genistein are not well established yet. This review aims to clarify the role of genistein on female and male reproductive functions in mammals. In females, at a high dose, genistein diminishes the ovarian activity regulating several pathway molecules, such as topoisomerase isoform I and II, protein tyrosine kinases (v-src, Mek-4, ABL, PKC, Syk, EGFR, FGFR), ABC, CFTR, Glut1, Glut4, 5α-reductase, PPAR-γ, mitogen-activated protein kinase A, protein histidine kinase, and recently circulating RNA-miRNA. The effect of genistein on pregnancy is still controversial. In males, genistein exerts an estrogenic effect by inducing testosterone biosynthesis. The interaction of genistein with both natural and synthetic endocrine disruptors has a negative effect on testis function. The positive effect of genistein on sperm quality is still in debate. In conclusion, genistein has a potentially beneficial effect on the mechanisms regulating the reproduction of females and males. However, this is dependent on the dose, the species, the route, and the time of administration.